Analisis Sistem Informasi Akuntansi Pada Pembayaran SPP Dan Tabungan Berbasis Web Pada SDS Duri Indah - Sri Wahyuningsih; Wahyumi Ekawanti; Pepi Permatasari; Sigit Nurcahyono (Universitas 17 Agustus 1945 Semarang, 2023)
SDS (Private Elementary School) Duri Indah Jakarta is one of the educational institutions which until now has not been computerized. Both in terms of payment and in terms of financial activities. Inputting and other activities are still done manually and recorded in a book as processing of student data. Data storage that is being carried out at this time is also still archived in a ledger, causing teachers and principals to have to record one by one the names of their students as a whole who have paid so that this can result in erroneous information regarding student payment and savings data and makes it difficult for teachers to find and provide the necessary data. Based on this, a web-based SPP and Savings payment system is needed. The stages of system development in making this information system use the prototyping method which starts from the planning stage, the analysis stage, the design stage, and the implementation stage, in the future it is hoped that the system created will make it easier for schools to control tuition payments and student savings.